International relations - Goldstein, Joshua S., 1952-; Pevehouse, Jon C., 1973- (Boston : Pearson Longman, 2012)
The bestselling text in its field, International Relations wins praise for being the most current and comprehensive introduction to international relations theory as well as security, economic, and global issues. From war and trade to human rights and the environment, this survey explores relations among states and the influence of transnational actors and events. Applying a broad range of theoretical perspectives to show students how to analyze current events, International Relations offers the best tools for understanding what is happening in the world today.
Includes bibliographical references and indexes.
Keywords: Go international; International office; International relations; Internationale economie; Internationale politiek; Internationale relaties